Relationship Between Triglycerides And Glucose Index (TyG) And Lipid Profile In Patients With Dyslipidemia Treated With Bay Leaf Extract [Syzygium Polyanthum (Wight) Walp] - Prianwari, Catur; Santi Syafril (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Background: Insulin Resistance (IR) causes a metabolic disorder including hyperglycemia, high blood pressure, and dyslipidemia. The purpose of the study was to assess the relationship of Triglycerides and Glucose Index (Tyg) decline relationship with lipid profile after bay leaf extract treatment in dyslipidemia patients. Method: Fifteen dyslipidemia patients were administered 2x200 mg salam leaf extract capsules for 30 days. Criteria dyslipidemia is defined as one of the following: total cholesterol level ≥ 240 mg/dL, triglyceride levels ≥150 mg/dL, LDL cholesterol levels ≥140 mg/dL, HDL cholesterol levels <40 mg/dL, or the use of lipid-lowering drugs. Blood samples lipid profile for biochemical tests were drawn in the morning after fasting 12 h. Anthropometric BMI and waist circumference measures were taken using standard procedures. The TG/HDL-C ratio was calculated by dividing the serum concentration of TG by HDL-C measured in mg/dL. TyG index was calculated based on formula: Ln [TG (mg/dL) x FG (mg/dL). Result: After 30 days of salam leaf extract treatment, there was a significant correlation of TyG reduction with parameters TC, LDL-C, TG, TG/HD ratio (p: 0.025*, p: 0.001*, p: 0.013*, sequentially) Conclusion: There is a significant correlation between Tyg reduction with TC, TG, and TG/HDL, which leads to a decrease in cardiovascular risk in dyslipidemia patients.